Integration of the Islamic Religious Education Curriculum in Building a Religious Culture at Mts At-Tibyan Deli Serdang - Ulum, Bahrul (MODELING: Jurnal Program Studi PGMI, 2024)
This study aims to explore and analyze how the integration of the Islamic Religious Education (PAI) curriculum can build a religious culture at MTS At-Tibyan Deli Serdang. By understanding the role of PAI in shaping students' character and religious values, this research is expected to provide constructive recommendations for the development of a more effective and relevant curriculum. This study uses a qualitative method. Data collection was carried out through observation, interviews, and document studies. The informants include the headmaster, the curriculum vice-principal, and PAI teachers. In analyzing the data, the researcher used qualitative analysis through steps of data presentation, data reduction, and drawing conclusions. The results of this study show that: 1) The integration of the Islamic Religious Education (PAI) curriculum at MTS At-Tibyan combines theory and practice, both in religious teaching and students' daily life. Through regular worship, the integration of Islamic values into general subjects, and an asrama-based learning model, MTS At-Tibyan has successfully created a generation that is not only academically intelligent but also has a strong religious character. This approach plays an important role in building a religious culture in the school, making PAI the foundation in shaping students' personalities in line with Islamic teachings. 2) The integration of the PAI curriculum at MTS At-Tibyan has had a significant impact on shaping the religious culture in the school. The holistic approach, which combines religious theory and its practical application in daily life, as well as the asrama-based teaching model and educators' role modeling, has succeeded in establishing religious habits. MTS At-Tibyan has not only shaped a generation with strong religious knowledge but also instilled Islamic values in their daily lives, creating a deep and sustainable religious culture both inside and outside of school. 3) The integration of the PAI curriculum at MTS At-Tibyan faces challenges related to students' inadequate diniyyah understanding and their adaptation to asrama life. To address these challenges, MTS At-Tibyan applies a comprehensive strategy, including intensive guidance for students who need a deeper understanding of diniyyah and gradual adjustment for those who are living in the asrama for the first time. Collaboration among the school, caretakers, teachers, and parents plays a key role in creating an environment that supports students' spiritual and academic development, ensuring the effective implementation of the PAI curriculum and the formation of strong religious character in the younger generation.